Impacts of cow body condition score during gestation on weaning performance of the offspring - Marques, R. S. (2016)
This experiment evaluated the impacts of cow body condition score (BCS) during gestation on productive parameters of the offspring. Three hundred multiparous, lactating, non-pregnant Angus × Hereford cows were assigned to a fixed-time artificial insemination (AI) protocol using semen from a single sire (d 0). Forty days after AI, cows were evaluated for pregnancy status via transrectal ultrasonography and BCS, and 100 pregnant cows (543±6 kg of BW, 6.6±0.3 yr of age, 4.83±0.06 of BCS, and 115±2 d postpartum) were selected for the experiment. Within these 100 cows, 20 cows had BCS ≥5.50 but ≤6.50 and were classified as adequate BCS (5.85±0.06; HBCS). The remaining cows had BCS ≤4.75 (4.52±0.03), and were divided into 4 groups (20 cows/group): LBCS (4.60±0.07), BCSG1 (4.43±0.07), BCSG2 (4.63±0.07), and BCSG3 (4.63±0.07). The HBCS and LBCS cows were managed to maintain their initial BCS throughout gestation. The BCSG1, BCSG2, and BCSG3 cows were managed to gain 1.50 BCS during the first, second, and third trimester of gestation, respectively, and maintain the resultant BCS until calving. Cow BCS was assessed again on d 102, 182, and 265. During the calving season (d 272-291), calf body weight (BW) was recorded within 3 h after birth. Only cows that met the BCS maintenance (within 0.50 of BCS change) and change (≥1.25 and ≤1.75 of BCS increase within the trimester) criteria were maintained in the experiment (HBCS, n =14; LBCS, n =14; BCSG1, n =14; BCSG2, n =15, BCSG3, n =15). On d 344, cow milk production was estimated by the weigh-suckle-weigh method, and calves were weaned on d 475. No differences were detected (P≥0.42) for calving rate, calf birth BW, and cow milk production. Weaning rate and calf age at weaning were also similar among BCS groups (P≥0.15). However, calf weaning BW was greater (P≤0.05) for BCSG2 and BCSG3 cows (265 and 262 kg, respectively; SEM =4) compared with HBCS and LBCS cows (248 and 249 kg, respectively; SEM =4), and similar (P≥0.20) among all other comparisons. These results suggest that offspring weaning BW is directly influenced by BCS gain of beef cows during the second and third trimesters of gestation.